The effectiveness of health promotion program services in improving exclusive breastfeeding coverage - Listi Tri Syafira; Fitriani Pramita Gurning; Dewi Agustina (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Exclusive breastfeeding is a key strategy to improve infant health because breast milk provides complete nutrition, supports growth, and protects infants from infectious diseases. Although national policies and health promotion programs have been implemented, exclusive breastfeeding coverage remains below the expected target in several areas, including the working area of the Biru Biru Community Health Center. Purpose: To analyze the effectiveness of promotional program services in increasing exclusive breastfeeding coverage in the working area of the Biru Biru Community Health Center. Method: A qualitative descriptive design was employed with a program evaluation approach based on the input-process-output framework. Data were collected through in-depth interviews, observation, and documentation involving health workers and breastfeeding mothers who were directly related to the exclusive breastfeeding promotion program. The data were analyzed through data reduction, data display, and conclusion drawing. NVivo 12 was used to assist the coding and organization of qualitative data Results: The input component was generally adequate, particularly in terms of health workers, facilities, and promotional media. However, several limitations were found, including incomplete written guidelines, limited program funding, and uneven participation among mothers. In the process component, health education, counseling, and mentoring activities were routinely implemented, although they were constrained by mothers’ low participation and health workers’ workload. In the output component, the program contributed to increased maternal knowledge and a more positive attitude toward exclusive breastfeeding, but the coverage had not yet reached the expected target. Conclusion: The exclusive breastfeeding promotion program at the Biru Biru Community Health Center has supported the improvement of maternal knowledge and awareness, but its effectiveness remains suboptimal. Strengthening program planning, increasing community participation, optimizing promotional media, and improving the role of health workers are needed to achieve better exclusive breastfeeding coverage.